STRESS AND PROBLEM OF CHILDREN OF ALCOHOLICS- THE INFLUENCE OF COPING STRATEGIES : A COMMUNITY BASED RESEARCH - GENESTA MARY GYSEL,; PARAMANANTHAM, (International Journal of Pharma and Bio Sciences, 2016)
The purpose of the study was to investigate the stress among children of alcoholics (COAs),their level of problems and their adopted coping strategies. A sample of 400 COAs (Male = 172: Female = 228) was identified through purposive sampling technique by AUDIT questionnaire. The results of the study showed that stress of COAs had a significant positive correlation with their problems. It was also found that coping was negatively correlated with problems and stress of COAs. It was revealed that demographic variables like mother’s education and mother’s income of alcohol addicted parent was negatively associated with problem levels, and father’s occupation was significantly associated with stress of COAs. The study therefore concluded that the parent’s alcohol addiction increases stress and problem of COAs and decreases their effective coping to them. It is recommended that guidance and counseling should be provided to COAs to assist in order to enhance effective coping to stress and problems.